The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0100-879x1997001200013
|View full text |Cite
|
Sign up to set email alerts
|

Aversive stimulation during the stress-hyporesponsive period does not affect the number of corticotroph cells in neonatal male rats

Abstract: Immunohistochemistry was used to evaluate the effects of neonatal handling and aversive stimulation during the first 10 days of life on the number of corticotrophs in the anterior lobe of the pituitary of 11-dayold male Wistar rats. Since adult rats handled during infancy respond with reduced corticosterone secretion in response to stressors and with less behavior inhibition in novel environments, we assumed that neonatal stimulation could affect pituitary morphology during this critical period of cell differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The central hypothesis of the current study is that neonatal stimulation might induce structural changes in the central nervous system, which would in turn account for the alterations observed in adult life. In order to explain the behavioral and neuroendocrine effects of early handling in an adult animal, it is plausible to raise the hypothesis that early-life stimulation leads to stable, probably structural, alterations, which could explain the behavioral and neuroendocrine effects of neonatal handling (Aguiar, Cadore, Padoin, Barbosa-Coutinho, & Lucion, 1997; Caldji et al, 2000; Hermel et al, 2001; Liu, Diorio, Day, Francis, & Meaney, 2000; Meaney et al, 1996; Sturrock, Smart, & Tricklebank, 1983; Vaid et al, 1997; Veenman et al, 1999). A trace left by the neonatal stimulation in the nervous system could be the cause of the behavioral changes observed in adulthood.…”
mentioning
confidence: 99%
“…The central hypothesis of the current study is that neonatal stimulation might induce structural changes in the central nervous system, which would in turn account for the alterations observed in adult life. In order to explain the behavioral and neuroendocrine effects of early handling in an adult animal, it is plausible to raise the hypothesis that early-life stimulation leads to stable, probably structural, alterations, which could explain the behavioral and neuroendocrine effects of neonatal handling (Aguiar, Cadore, Padoin, Barbosa-Coutinho, & Lucion, 1997; Caldji et al, 2000; Hermel et al, 2001; Liu, Diorio, Day, Francis, & Meaney, 2000; Meaney et al, 1996; Sturrock, Smart, & Tricklebank, 1983; Vaid et al, 1997; Veenman et al, 1999). A trace left by the neonatal stimulation in the nervous system could be the cause of the behavioral changes observed in adulthood.…”
mentioning
confidence: 99%
“…Previous studies (1-3) have shown that several procedures which stimulate pups during the neonatal period appear to affect the animal's reaction to stress stimulation in adult life, but not the basal quantities of hormones (5,6) or the number of corticotroph cells in the pituitary (17). Similarly, our results showed that neonatal handling induced no change in the number of neurons immunoreactive to tyrosine hydroxylase in hypothalamic nuclei of animals that were not submitted to new stressful stimuli before the cell count.…”
mentioning
confidence: 99%
“…First-Episode Psychosis (FEP) groups were reported to have larger PGs than healthy controls in several (Atmaca 2014;Pariante et al 2004;Takahashi et al 2013) but not all (Gruner et al 2012;Habets et al 2012) studies, and so were their first-degree relatives (Aiello et al 2012;Mondelli et al 2008). One hypothesis is that larger PG volume is due to increased number and size of corticotropes and HPA hyperreactivity (Axelson et al 1992;Pariante et al 2004), although support for this hypothesis from animal studies is limited (Aguiar et al 1997;Füchsl et al 2013). HPA hyperreactivity, in turn, could affect the expression of genes critical in brain development like brain-derived neurotrophic factor (BDNF), especially during puberty, and lead to the onset of psychosis (Aiello et al 2012;Borges et al 2013).…”
Section: Inconsistencies In Mri Studies Of Psychopathologiesmentioning
confidence: 99%